2020
DOI: 10.1007/s00253-020-10420-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity following vaccination with a recombinant multiple-epitope protein of bovine herpesvirus type I in a rabbit model

Abstract: Bovine herpesvirus type 1 (BoHV-1) causes considerable economic losses to the cow industry. Vaccination remains an effective strategy to control the diseases associated with BoHV-1. However, live vaccines present safety concerns, especially in pregnant cows; thus, nonreplicating vaccines have been developed to control the disease. The envelope glycoproteins of BoHV-1 induce a protective immune response. In this work, selected epitopes on glycoproteins gD, gC, and gB were constructed in triplicate with linker p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Other studies in which a candidate BoHV-1 vaccine composed of envelope glycoprotein subunits was evaluated in different animal models, have shown comparable or lower antibody titers than those obtained in our experiment at day 42 ( Figure 2 ) [ 10 , 31 , 32 , 33 , 34 , 35 ]. Therefore, our results strongly suggest that our vaccine formulation has the potential to be an effective immunogen for cattle.…”
Section: Discussionsupporting
confidence: 72%
“…Other studies in which a candidate BoHV-1 vaccine composed of envelope glycoprotein subunits was evaluated in different animal models, have shown comparable or lower antibody titers than those obtained in our experiment at day 42 ( Figure 2 ) [ 10 , 31 , 32 , 33 , 34 , 35 ]. Therefore, our results strongly suggest that our vaccine formulation has the potential to be an effective immunogen for cattle.…”
Section: Discussionsupporting
confidence: 72%
“…The AAYAAY linker was used to integrate the MHC-I/II binding epitopes to produce MhpMEV; other linkers, including AAY [ 28 ], GPGPG [ 27 ], EAAAK [ 29 ], and GGGGS [ 30 ], have been used in previous studies, while the AAYAAY linker was reported to induce a higher level of specific antibodies [ 30 ]. For the structural analysis, MhpMEVC6His can be regarded as an artificial protein, because no homologous protein was found in the NCBI nr database.…”
Section: Discussionmentioning
confidence: 99%